Progressive exercise compared with best practice advice, with or without corticosteroid injection, for the treatment of patients with rotator cuff disorders (GRASP): a multicentre, pragmatic, 2 × 2 factorial, randomised controlled trial. Issue 10298 (31st July 2021) - Hopewell, Sally; Keene, David J; Marian, Ioana R; Dritsaki, Melina; Heine, Peter; Cureton, Lucy; Dutton, Susan J; Dakin, Helen; Carr, Andrew; Hamilton, Willie; Hansen, Zara; Jaggi, Anju; et al.
Summary: Background: Corticosteroid injections and physiotherapy exercise programmes are commonly used to treat rotator cuff disorders but the treatments' effectiveness is uncertain. We aimed to compare the clinical effectiveness and cost-effectiveness of a progressive exercise programme with a single session of best practice physiotherapy advice, with or without corticosteroid injection, in adults with a rotator cuff disorder. Methods: In this pragmatic, multicentre, superiority, randomised controlled trial (2 × 2 factorial), we recruited patients from 20 UK National Health Service trusts. We included patients aged 18 years or older with a rotator cuff disorder (new episode within the past 6 months). Patients were excluded if they had a history of significant shoulder trauma (eg, dislocation, fracture, or full-thickness tear requiring surgery), neurological disease affecting the shoulder, other shoulder conditions (eg, inflammatory arthritis, frozen shoulder, or glenohumeral joint instability), received corticosteroid injection or physiotherapy for shoulder pain in the past 6 months, or were being considered for surgery. Patients were randomly assigned (centralised computer-generated system, 1:1:1:1) to progressive exercise (≤6 sessions), best practice advice (one session), corticosteroid injection then progressive exercise, or corticosteroid injection then best practice advice. The primary outcome was the Shoulder Pain and Disability Index (SPADI) score over 12 months, analysed on an intention-to-treat basis (statistical significance set at 1%). The trial was registered with the International Standard Randomised Controlled Trial Register, ISRCTN16539266, and EuDRACT, 2016-002991-28. Findings: Between March 10, 2017, and May 2, 2019, we screened 2287 patients. 708 patients were randomly assigned to progressive exercise (n=174), best practice advice (n=174), corticosteroid injection then progressive exercise (n=182), or corticosteroid injection then best practice advice (n=178). Over 12 months, SPADI data were available for 166 (95%) patients in the progressive exercise group, 164 (94%) in the best practice advice group, 177 (97%) in the corticosteroid injection then progressive exercise group, and 175 (98%) in the corticosteroid injection then best practice advice group. We found no evidence of a difference in SPADI score between progressive exercise and best practice advice when analysed over 12 months (adjusted mean difference −0·66 [99% CI −4·52 to 3·20]). We also found no evidence of a difference between corticosteroid injection compared with no injection when analysed over 12 months (−1·11 [–4·47 to 2·26]). No serious adverse events were reported. Interpretation: Progressive exercise was not superior to a best practice advice session with a physiotherapist in improving shoulder pain and function. Subacromial corticosteroid injection provided no long-term benefit in patients with rotator cuff disorders. Funding: UK National Institute for Health Research Technology Assessment Programme.